IMPROVING TEACHER COMPETENCE IN ONLINE LEARNING AT SMAN 1 BANJARMASIN - Muhlisah, Muhlisah (Universitas Lambung Mangkurat, 2024)
The main challenge faced is how teachers can adapt and enhance their competencies in managing online classes to achieve optimal learning outcomes. This study aims to describe teacher competencies in online learning at SMAN 1 Banjarmasin, which is crucial in addressing the challenges of ensuring effective learning amidst limited direct interaction. The research employs a qualitative method, with primary data obtained through direct observation and interviews, and secondary data comprising relevant documents. Data collection techniques include observation, interviews, and documentation. Data analysis was conducted through processes of reduction, data presentation, and verification. The results show that teachers' competencies in online learning meet the required standards for effective implementation, ensuring the success of online education.